Motivasi Intrinsik dan Ekstrinsik dalam Belajar Al-Qur'an: Perspektif Ibu Rumah Tangga di Lhokseumawe - Rahmat, Aulia (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2024)
ABSTRACT ENGLISH:This study aims to identify housewives' intrinsic and extrinsic motivations for reading the Qur'an. This is a qualitative study conducted in Gampong Uteun Bayi, Banda Sakti District, Lhokseumawe. Data for this study were gathered through observation and in-depth interviews with 20 housewives who were actively engaged in learning to read the Qur'an. The data analysis techniques used in this study included data collection, data presentation, and conclusion drawing. The findings revealed that intrinsic motivation factors in housewives learning to read the Qur'an include the desire to be able to read the Qur'an properly and correctly, to teach children and grandchildren, to reap the benefits of reading the Qur'an, to prepare for the afterlife, and to invest in the right place. The extrinsic motivation discovered includes an expert teacher, a flexible schedule, being invited by friends, gathering for positive activities, and brotherhood in the majlis. In this study, spiritual and social factors dominate both the intrinsic and extrinsic motivation of housewives to learn the Qur'an. Following up on the findings of this study, discussions about the motivation of housewives to learn the Qur'an in Lhokseumawe City should be held in order to have a positive impact on Qur'anic learning. ABSTRACT INDONESIAN:Tujuan penelitian ini adalah untuk menemukan dorongan intrinsik dan eksternal ibu rumah tangga untuk belajar membaca Al-Qur'an. Penelitian kualitatif ini dilakukan di Gampong Uteun Bayi, yang terletak di Kecamatan Banda Sakti, Lhokseumawe. Data untuk studi ini dikumpulkan melalui observasi dan wawancara menyeluruh dengan dua puluh ibu rumah tangga yang aktif terlibat dalam kegiatan belajar membaca Al-Qur'an. Dalam penelitian ini, metode analisis data terdiri dari pengumpulan data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa motivasi intrinsik ibu rumah tangga untuk belajar membaca Al-Qur'an adalah keinginan untuk membaca Al-Qur'an dengan baik dan benar, mengajarkannya kepada anak cucu, memperoleh pahala dari membaca Al-Qur'an, mempersiapkan diri untuk akhirat, dan memberikan infaq pada tempat yang tepat. Faktor eksternal yang ditemukan termasuk guru yang hebat, jadwal yang fleksibel, berteman dengan orang lain, berkumpul untuk hal-hal positif, dan persaudaraan dalam komunitas. Faktor spiritual dan sosial mendominasi motivasi ibu rumah tangga dalam belajar Al-Qur'an dalam studi ini.